(untitled) - Anderson, Edwin P. (New York, 1983)
Provides practical guidance in the selection, installation, operation, and maintenance of electric motors using illustrations and simplified explanations for both technical and nontechnical persons.
Keywords: Electric motors,Động cơ điện